One Supreme Court supremacy, inferiority, and the judicial power of the United States - Pfander, James E. (New York ; Oxford : Oxford University Press, 2009)
In offering a general account of the Court as department head, Pfander takes up such important debates in the federal courts' literature as Congress's power to strip the federal courts of jurisdiction to review state court decisions, its authority to assign decision-making authority to state courts, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Supreme Court; Judicial power -- United States; Political questions and judicial power -- United States; Courts -- United States; Executive power -- United States; Separation of powers -- United States; War and emergency powers -- United States